Finansiële voorspraak: ideaal of werklikheid? - E. Greeff; I. Treadwell (AOSIS, 1998)
It seems that in spite of soaring medical costs and a poor economic climate, financial advocacy for patients is not general practice. A question that arises is what part nurses play and what their perceptions on financial advocacy for patients are. A non-experimental descriptive study was done to determine what nurses' perceptions on financial advocacy are and how knowledgeable they are about the costs of disposable dispensary stock. Thirty patient accounts were analysed and questionnaires were completed by a convenience sample of thirty two registered nurses who had permanent appointments in high care or intensive care units. Results : On average nurses control the utilization of 15,8% of each of the prescription accounts. Only 12,5% of respondents had formal education on their responsibility in keeping costs low. The majority (60%) of the 50% of respondents who had previously received information had performed financial advocacy although 94% agreed that they have the responsibility to do so. A mere 9% was achieved on the knowledge of the costs involved in using consumable products from the dispensary.